Viromes of Coastal Waters of the North Caspian Sea: Initial Assessment of Diversity and Functional Potential - Madina S. Alexyuk; Yurij S. Bukin; Tatyana V. Butina; Pavel G. Alexyuk; Vladimir E. Berezin; Andrey P. Bogoyavlenskiy (Diversity, 2023)
In recent years, the study of marine viromes has become one of the most relevant areas of geoecology. Viruses are the most numerous, genetically diverse and pervasive biological entities on Earth, including in aquatic ecosystems. Information about viral diversity in aquatic ecosystems remains limited and requires more research. This work provides the first-ever look at the current DNA virome of the Northern Caspian Sea. A comparison with other freshwater and marine viromes revealed that the North Caspian Sea virome has the greatest similarity with those of the Baltic Sea and Lake Baikal. The study described in this article expands the knowledge about aquatic viromes and provides key data for a more comprehensive analysis of viruses circulating in the Caspian Sea, the largest inland body of water on Earth.